Integrated global and unique metabolic characteristics to reveal the intervention effect of Yiyi decoction on acute pancreatitis. - Guanwen Gong; Yongping Wu; Yanwen Jiang; Yuan Cao (PLoS ONE)
Yiyi decoction is a Chinese herbal formula for the treatment of acute pancreatitis that has been used in clinical practice for decades. A previous study has suggested that resveratrol, emodin, rhein and their derivatives might be the potential pharmacodynamic components in Yiyi decoction, and researchers have proposed that resveratrol, emodin and rhein are candidate markers for quality control. The present study investigated the intervention effect of Yiyi decoction and its effective components on murine acute pancreatitis using metabolomic approach that integrated global and unique metabolic characteristics. First, serum metabolomics based on the platform of ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry was performed to assess metabolic changes in experimental acute pancreatitis. Second, an in-depth analysis of bile acid metabolism was performed based on an in-house database. Finally, an integrated analysis of the intervention effect of Yiyi decoction and its effective components in response to these metabolic perturbations was performed. As a result, 39 potential biomarkers for the pathogenesis of acute pancreatitis, mainly phospholipids, fatty acids, bile acids and lipoylcarnitines, were screened and annotated. Integrated analysis revealed that the metabolic disorders in acute pancreatitis mice were reversed by Yiyi decoction primarily via regulating glycerophospholipid metabolism, bile acid biosynthesis, carnitine synthesis and fatty acid metabolism. Yiyi decoction components may effectively target the migratory metabolome. Histopathological and biochemical analyses suggested that Yiyi decoction maintained the gut barrier function and inhibited inflammatory cytokines, thus exert anti-acute pancreatitis effects. The present study utilized an approach that integrated global and unique metabolic characteristics to elucidate the underlying mechanisms of Chinese herbal formulas from a metabolomics perspective.